Simplified Space Vector Pulse Width Modulation Based on Switching Schemes with Reduced Switching Frequency and Harmonics for Five Level Cascaded H-Bridge Inverter - Sirisha, B.; Satishkumar, Dr. P. (International Journal of Advances in Applied Sciences, 2018)
This paper presents a simplified control strategy of SVPWM with a three segment switching sequence and 7 segment switch frequency for high power multilevel inverter. In the proposed method, the inverter switching sequences are optimized for minimization of device switching sequence frequency and improvement of harmonic spectrum by using the three most derived switching states and one suitable redundant state for each space vector. The proposed 3-segment sequence is compared with conventional 7-segment sequence similar for five level Cascaded H-Bridge inverter with various values of switching frequencies including very low frequency. The output spectrum of the proposed sequence design shows the reduction of device switching frequency and states current and line voltage. THD this minimizing the filter size requirement of the inverter, employed in industrial applications. WhereÂ  sinusoidal output voltage is required.